Pengaruh Model Pembelajaran Inside Outside Circle Terhadap Hasil Belajar IPS Siswa Kelas IV SDN Gugus 01 Kecamatan Sakra Timur Tahun Pelajaran 2020/2021 - Inangda, Neni Tiyas; Safruddin, Safruddin; Oktaviyanti, Itsna (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2021)
This study is an experimental study (Quasi Experiment) which aims to determine the effect of the Inside Outside Circle model on the learning outcomes of fourth grade students at SDN Gugus 01, Sakra Timur District in Social Studies Learning in the 2020/2021 academic year. The design of this study used the Noneequivalent control group design. The population in this study were all fourth-grade students of SDN Gugus 01, East Sakra District. The sampling technique used is purposive sampling, the samples are class IV SDN 1 Lepak as the experimental class and class IV SDN 3 Lepak as the control class. Data collection methods used in the form of observation and test learning outcomes. Student learning outcomes data are in the form of pretest and posttest. Normality test is carried out by calculating data in the form of pretest and posttest results, then after the data is normally distributed, homogeneity test is carried out obtained from the results of posttest data calculations, then hypothesis testing is carried out with t test using student posttest data calculations. Based on the learning outcomes data analyzed using the t-test (t-test) obtained tcount of 4.037 while ttable of 2.052 at the 5% confidence level. This explanation shows that tcount is greater than ttable so it can be concluded that Ha is accepted and H0 is rejected. shows that there is an influence of the Inside Outside Circle model on student learning outcomes. Furthermore, in the effect size test with the acquisition of a value of 1.125 with high criteria because > 1.00 based on the results of the calculation of the effect size value of Cohen's d